2020
DOI: 10.3855/jidc.11983
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of real life data of HCV from Turkey south region

Abstract: Introduction: This study investigated demographic characteristics and the prevalence of viremia among anti-HCV-positive patients. Methodology: Hospital records of adult patients with anti-HCV positivity between June 2016 and October 2018 were screened retrospectively. Demographic characteristics, genotype distribution, history of injection drug use (IDU), treatment data of HCV RNA-positive patients were investigated. Results: The rate of anti-HCV seropositivity was 1.7% and 54.5% of these were vire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Even though most of the patients in this study who were 40 or older and had any type of disease had genotype 1b, the authors thought that infection through blood transfusion could be the main cause in this patient group, while the fact that genotype 3 was most common in younger patients with substance use disorder showed similarities to our study. 28 It is remarkable that genotype 3 (44.1%) and genotype 1a (41.95%), the 2 most common types in this study, are similarly the 2 most common subtypes in the studies conducted in Turkey until now. It is also remarkable that the dominant type varies with respect to geographical regions.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Even though most of the patients in this study who were 40 or older and had any type of disease had genotype 1b, the authors thought that infection through blood transfusion could be the main cause in this patient group, while the fact that genotype 3 was most common in younger patients with substance use disorder showed similarities to our study. 28 It is remarkable that genotype 3 (44.1%) and genotype 1a (41.95%), the 2 most common types in this study, are similarly the 2 most common subtypes in the studies conducted in Turkey until now. It is also remarkable that the dominant type varies with respect to geographical regions.…”
Section: Discussionmentioning
confidence: 51%
“…80% of HCV genotype 1 cases are HCV genotype 1b. 5,21,27,28 Even though there aren't many studies showing that genotypes vary among PWID in Turkey, HCV genotypes 3 and 1 are the most common, with rates of 58.6% and 50.4% to 61%, respectively. [29][30][31] This difference in genotypic distribution may be due to common needle sharing within the PWID group, as well as different immunological mechanisms that help the persistence of different genotypes in patients with PWID.…”
Section: Introductionmentioning
confidence: 99%
“…19 Adana ilinde yapılan çalışmada 40 yaşından küçük hastalarda en yaygın genotip 3 ve 40 yaşından büyüklerde genotip 1b tespit edilmiştir. 20 İzmir ilinde yapılan çalışmada genotip 1b ile enfekte hastaların yaş ortalaması, genotip 1a, genotip 3 ve genotip 4 ile enfekte hastaların yaş ortalamasından yüksek bulunmuştur. 17 Giresun ilinde yapılan çalışmada ise; yaş ortalamalarının genotip 1b'de 1a ve 3'ten, genotip 1a'da ise genotip 3'ten anlamlı oranda daha yüksek olduğu saptanmıştır.…”
Section: Discussionunclassified
“…25 Results of similar studies conducted in Turkey indicate that HCV-RNA was not investigated in 30%-40% of the patients who had positive anti-HCV results. 26,27 Investigation of HCV screening in a tertiary care hospital in Turkey showed that 95 patients were positive for anti-HCV and that HCV-RNA was not investigated in 47% of these patients. 28 Similarly, the results of another Turkish study showed that HCV-RNA was not tested in 51% of the patients who had positive anti-HCV results.…”
Section: Discussionmentioning
confidence: 99%